Memória e transculturação no Pampa: um estudo da obra Figura na sombra de Luiz Antonio de Assis - Farias, Wenderson Pinto (2023)
Luiz Antonio de Assis Brasil is one of the great names in Brazilian literature today for writing novels in which the history of Brazil, more specifically of Rio Grande do Sul, is the north for the discussion of subjects present in the official historical discourse. In this perspective, Assis Brasil brings to light a fiction that raises reflection on contemporary themes, real-life characters relegated to oblivion and the richness of contact between different peoples and their cultures. Thus, this master's thesis proposes the reading and analysis of the novel Figure in the Shadow, part of the series Visitors to the South, with regard to the distant life of Aimé Bonpland. In the investigation, the memories and transculturation experienced by this character are observed. The observation of these aspects in the work studied aims to contribute to the appreciation of Latin American fiction in the academic context and to the contribution to the studies of literary criticism